The Critical Factors that Influence Dividend Payout Ratio on Pro-Cyclical and Non-Cyclical Sector Companies - David Santoso; Helen Adriana Wijaya; Jason Ferdianto Diharjo; Sugiarto Sugiarto; Agus Salim (Research Center and Case Clearing House PPM School of Management, 2026)
Pro‑cyclical and non‑cyclical sectors generate markedly different revenue patterns, a distinction that may influence firms’ willingness to share profits with investors. This study examines whether ownership structure and key financial variables influence dividend policy in Indonesia’s pro-cyclical manufacturing and non-cyclical consumer goods industries. Using a balanced panel of 435 firm-year observations (2015–2019) and fixed-effects panel regression, we examine the impact of family ownership, managerial compensation, leverage, and profitability on the dividend payout ratio. Sector‑specific results emerge. In consumer‑goods companies, higher managerial compensation significantly increases the dividend payout ratio, whereas greater leverage dampens it; family ownership and profitability are insignificant. In manufacturing firms, family ownership increases the dividend payout ratio, while leverage and profitability decrease it; managerial compensation has no significant impact. The findings help income‑oriented investors select suitable sectors, guide regulators in tailoring governance codes, and extend agency and signaling research to contrasting industry characteristics.